Simulation study of modified compact microstrip interdigital bandpass filter with wide stopband for L-band applications - Sahu B.; Meshram M.K.; Singh S.P.; Tripathi P. (My University, 2025)
In this paper, a modified microstrip interdigital bandpass filter (IBPF) with a pair of spurlines and defected ground structure (DGS) containing stepped impedance resonator (SIR) is proposed. A combination of spurlines and SIR-shaped DGS is used to obtain wide stopband which is the result of band notched characteristics of spurline and harmonics suppression characteristics of DGS. The 3-dB impedance bandwidth of the proposed filter is 1.153 GHz (79%) and covers the frequency range 0.885-2.038 GHz. The proposed filter is compact having size of 0.107 λ0 × 0.075 λ0, where λ0 is the free space wavelength at the centre frequency (f0) of 1.46 GHz. The compact, wideband BPF with wide stopband has stopband attenuation better than 14 dB upto the frequency range of approximately six times the centre frequency of the desired passband. The insertion loss value of the proposed filter varies from 0.12-0.57 dB over its operating frequency band. © 2015 IEEE.